Analisis terhadap Putusan Wanprestasi Nomor 4040 K/Pdt/2023 - Marsya Ainun Kholila; Cut Anastasya Nurul Hilal; Geal Aditya Christian; Lia Risqi Ananda (Universitas Wahid Hasyim, 2024)
This research aims to analyze the court's decision regarding the case of Afrizal who was declared a defendant in a default case. The main focus of the study is to identify whether the elements of breach of contract, such as unfulfilled obligations, unfairness of the defendant, and the resulting legal consequences, have been fulfilled in accordance with the provisions of civil law in Indonesia. The research method used is a normative juridical approach with analysis of decision documents, related regulations, and civil law literature. The results of the analysis show that the court considers the substantive aspects of the agreement, the evidence left behind, and the existence of peace efforts before the case is brought to court. The verdict stated that Afrizal was proven to have committed a breach of contract based on negligence in fulfilling contractual obligations which caused losses to the plaintiff. This research concludes that the decision is in accordance with civil law principles and emphasizes the importance of upholding justice in similar cases in the future.